REVITALISASI SPIRIT PEMBELAJARAN NABAWI: ADAPTASI METODE MENGAJAR KONTEMPORER PERSPEKTIF AL-QUR’AN DAN HADITS RIWAYAT IMAM BUKHARI - Rizki Lailatul Khilwa, Amalia; Ulul Azmi, M.; Arju Mushaffa; Amelia, Fatma; Ludviana, Vieke; Nur Azizah, Farida; Sholikhah, Mar’atus (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
We can see the flexibility and universality of the Qur'an in today's dynamic era as an example in human life which is increasingly developing. Likewise, the hadith of the Prophet Muhammad saw contained teaching values such as education. The method used by the Prophet Muhammad SAW in conveying several hadiths to his friends is part of education. Educational methods in Islam can be interpreted as a step or way of conveying the main teachings based on certain assumptions in order to achieve educational ideals and goals. In this case, the method itself plays a role because education itself without a method of delivery will experience problems. The aim of this research is to discuss problems related to interesting learning methods seen from the perspective of Islamic education, especially in the Al-Quran and Hadith tarbawi. The method used by researchers is a qualitative method, a type of literature study. The results of this research show that: there are many types of interesting learning methods, mentioned in the perspective of Al-Quran and Hadith verses, that the qishah method is found in the Al-Qur'an, Surah Yusuf, verse 3. Meanwhile, the drill method is found in the Al-Qur'an, Surah Al-Qiyamah, verses 16-18. The qishah and drill methods are also mentioned in the perspective of studying the hadiths narrated by Bukhari, which also contain teaching values and wisdom in the form of inspirational stories and very meaningful teachings.